A systematic review and network meta-analysis of cardiovascular safety of benzbromarone compared to febuxostat and allopurinol in patients with gout - Lin, Ting-Syuan; Lin, Yen-Liang; Hsu, Chiu-Hao; Hsieh, Song-Chou; Shau, Wen-Yi; Yang, Wei-Shiung; Chen, Chi-Ling (Frontiers in Cardiovascular Medicine, 2025)
BackgroundGout is caused by hyperuricemia and is associated with cardiovascular diseases. Treatment for hyperuricemia primarily involves urate-lowering medications. Some trials showed higher cardiovascular mortality rates with febuxostat compared to allopurinol in gout patients. However, data on the cardiovascular safety of benzbromarone compared to allopurinol is limited, and there is no data comparing benzbromarone to febuxostat. This study aims to assess the cardiovascular safety of benzbromarone, febuxostat, and allopurinol in gout patients.MethodsA comprehensive search was conducted across PubMed and EMBASE from their inception to August 2024. Inclusion criteria were randomized controlled trials (RCTs) and cohort studies including adult patients with the diagnosis of gout, with urate-lowering medications. The outcome was the incidence of major adverse cardiovascular events. This systematic review and network meta-analysis were recorded in INPLASY with the ID INPLASY202460049.ResultsA total of 176 studies were identified through the database search. There were 119 articles identified in EMBASE and 57 articles identified in PubMed. Following screening and review, 17 qualified studies (5 RCTs) were included in the network meta-analysis. The relative cardiovascular event risk (risk ratio, RR) for benzbromarone compared to febuxostat is 0.82 (95% CI 0.61–1.09), and for benzbromarone compared to allopurinol, the RR is 0.87 (95% CI 0.75–1.01). The RR for febuxostat compared to allopurinol is 1.08 (95% CI 0.97–1.20).ConclusionOur network meta-analysis suggests a subtle trend indicating a lower risk of cardiovascular events for benzbromarone compared to both febuxostat and allopurinol in gout patients, although not statistically significant.Systematic Review Registrationhttps://inplasy.com/inplasy-2024-6-0049/, identifier INPLASY202460049.